Brand admiration : building a business people love - Park, C. Whan; MacInnis, Deborah J.; Eisingerich, A. B. (Andreas B.) (Wiley, 2016)
"Brand Admiration uses deep research on consumer psychology, marketing, consumer engagement and communication to develop a powerful, integrated perspective and innovative approach to brand management. Using numerous real-world examples and backed by research from top notch academics, this book describes how companies can turn a product, service, corporate, person or place brand into one that customers love, trust and respect; in short, how to make a brand admired. The result? Greater brand loyalty, stronger brand advocacy, and higher brand equity. Admired brands grow more revenue in a more efficient way over a longer period of time and with more opportunities for growth. The real power of Brand Admiration is that it provides concrete, actionable guidance on how brand managers can make customers (and employees) admire a brand. Admired brands don't just do the job; they offer exactly what customers need (enabling benefits), in way that's pleasing, fun, interesting, and emotionally involving (enticing benefits), while making people feel good about themselves (enriching benefits). Providing these benefits, called 3 Es, is foundational to building , strengthening and leveraging brand admiration. In addition, the authors articulate a common-sense and action based measure of brand equity, and they develop dashboard metrics to diagnose if there are any 'canaries in the coal mine', and if so, what to do next. In short, Brand Admiration provides a coherent, cohesive approach to helping the brand stand the test of time. A well-designed, well-managed brand becomes a part of the public consciousness, and ultimately, a part of the culture. This trajectory is the fruit of decisions made from an integrated strategic standpoint. This book shows you how to shift the process for your brand, with practical guidance and an analytical approach"--